The Risk of Epilepsy After Febrile Seizure Recurrences Within 24 h. - Gencpinar, Pinar; Arican, Pinar; Aleyova, Nergiz; Dündar, Nihal O.; Direk, Meltem C.; Okuyaz, Çetin; Bektaş, Ömer; Yüksel, Merve F.; Yılmaz, Ünsal; Edizer, Selvinaz; Ünalp, Aycan; Haspolat, Şenay (Journal of Pediatric Neurosciences)
Abstract: Purpose: Although febrile seizure is widely believed to be mostly benign, there is a risk of having recurrent febrile seizures and potentially a risk of developing epilepsy after an initial febrile seizure. The aim of this study is to assess the risk of developing epilepsy after occurrence of febrile seizures, more than one seizure during the febrile illness. Materials and Methods: This retrospective multicentric study was conducted on children with a diagnosis of a febrile seizure occurring with more than one seizure during the febrile illness. Patients with an age range of one month–18 years were included in the study if they had a history of febrile seizure with more than one seizure during the febrile illness and followed clinically for at least six months. Results: Of the 204 patients, their median age was 27 months (IQR: 16–42). The median follow-up time was 15 months (IQR: 12–25). Sixty-three (24%) patients received intermittent prophylaxis with rectal diazepam. One hundred and seven (52%) patients received continuous prophylaxis. During follow-up, 36 (18%) patients developed epilepsy. Conclusion: We concluded that febrile seizures occurring of more than one seizure during the febrile illness are not associated with an increased risk of epilepsy.